Islamic perspectives on twentieth-century English literature - Hasan, Md. Mahmudul (International Institute of Islamic Thought (East and South East Asia), 2017)
There is a tendency to regard (English) literature as beyond the pale of religion and conventional morality. Advocates of the postulates of the art for art’s sake school are perhaps predisposed to dismiss academic endeavours of relating Islam to literary discussion. This is despite the fact that there are millions of Muslim students of English literature who are exposed to Western/(neo-) European values and cultural assumptions through the subject. The conventional, impressionable teaching and learning of English literary texts, de-contextualising them and failing to distinguish between the good and the evil they carry contribute to the proliferation of alien views and ways of life in non-Western, Muslim-majority societies. This book represents a humble attempt to go a few steps beyond the conventional mode of English literary criticism. It looks at the subject with a sense of discrimination and is intended to enhance learners’ religio-cultural understanding and competence. It aims to help students conceptualise the world as presented in English texts through the prism of Islamic teachings. The arguments in this book show the concrete relevance of Islam to issues discussed in the selected works of major authors of twentieth-century English literature, such as: Joseph Conrad (1857 – 1924), Rudyard Kipling (1865 – 1936), Virginia Woolf (1882 – 1941), T. S. Eliot (1888 – 1965), W. H. Auden (1907 – 1973) and Doris Lessing (1919 – 2013). It is a useful reference material for those who teach and study twentieth-century English literature.